2014
DOI: 10.1073/pnas.1410980111
|View full text |Cite
|
Sign up to set email alerts
|

Translocalized IgA mediates neutralization and stimulates innate immunity inside infected cells

Abstract: IgA is the most prevalent antibody type on mucosal surfaces and the second most prevalent antibody in circulation, yet its role in immune defense is not fully understood. Here we show that IgA is carried inside cells during virus infection, where it activates intracellular virus neutralization and innate immune signaling. Cytosolic IgA-virion complexes colocalize with the high-affinity antibody receptor tripartite motif-containing protein 21 (TRIM21) and are positive for lysine-48 ubiquitin chains. IgA neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 33 publications
0
74
0
1
Order By: Relevance
“…The binding of TRIM21 itself to antibody occurs with high affinity and only a few antibodies are necessary to provoke a neutralization response11. TRIM21 has highest affinity for IgG but is also capable of binding IgM and IgA, albeit with reduced affinity (17 μM and 50 μM respectively to monomeric PRYSPRY domain)12319. Given that full-length dimeric TRIM21 increases affinity to IgG by ~375-fold, the functional affinity to IgA and IgM is likely to be submicromolar.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of TRIM21 itself to antibody occurs with high affinity and only a few antibodies are necessary to provoke a neutralization response11. TRIM21 has highest affinity for IgG but is also capable of binding IgM and IgA, albeit with reduced affinity (17 μM and 50 μM respectively to monomeric PRYSPRY domain)12319. Given that full-length dimeric TRIM21 increases affinity to IgG by ~375-fold, the functional affinity to IgA and IgM is likely to be submicromolar.…”
Section: Discussionmentioning
confidence: 99%
“…While Fc receptors are highly selective in regard to isotype and subtype binding, TRIM21 not only binds IgG but also IgM and IgA (32,35). Interestingly, the binding site for TRIM21 on IgA and IgM overlaps with that of Fc a receptor I (FcaRI), Fca/l receptor, pIgR, as well as several pathogen-produced Fc receptors (61)(62)(63)(64)(65)(66)(67)(68).…”
Section: Trim21 Has Broad Antibody Isotype Specificitymentioning
confidence: 99%
“…In contrast, the binding of TRIM21 is pH independent and does not require protonation. TRIM21 is capable of binding all IgG subclasses with nM affinity (Keeble et al, 2008) and has also been shown to bind IgM (Mallery et al, 2010) and IgA (Bidgood et al, 2014), however with lower affinities of 17 and 50 μM, respectively.…”
Section: The Role Of Trim21 In Innate Immunitymentioning
confidence: 99%